Effectiveness of Pinrang Regency Regional Regulation on Entertainment Tax in an Effort to Increase Regional Original Revenue - Sri Handayani; Asram A.T. Jadda; Wahyu Rasyid; Asrul Hidayat (Journal of Law Justice (JLJ), 2025)
This research aims to determine and analyze the implementation of Pinrang Regency Regional Regulation Number 9 of 2018 which amends Regional Regulation Number 3 of 2011 concerning Entertainment Tax, with a focus on efforts to increase local original income. Apart from that, this research also aims to understand the factors that influence the effectiveness of implementing these Regional Regulations. This study applies a normative-empirical research approach. This study applies data analysis through a qualitative descriptive approach, which aims to describe or photograph an issue related to existing patterns and challenges. Then, the researcher presents information that has been collected from literature research and interviews, which can be used as a reference in solving problems. The findings from this research indicate that the implementation of Pinrang Regency Regional Regulation Number 9 of 2018 regarding Entertainment Tax in order to increase Regional Original Income (PAD) is still not optimal. Several factors that influence the effectiveness of implementing these regulations consist of internal, external, regulatory and legal culture factors. Internal factors include limited human resource capabilities and infrastructure, such as a lack of training for officers and a lack of technology that supports the tax system. External factors include low awareness and involvement of business actors in the entertainment sector, the economic situation at the local level, and geographical constraints that complicate the monitoring process.